Quorum Sensing and Quorum Quenching in the Mediterranean Seagrass Posidonia oceanica Microbiota - Blanchet, Elodie; Prado, Soizic; Stien, Didier; Oliveira da Silva, Jocivânia; Ferandin, Yoan; Batailler, Nicole; Intertaglia, Laurent; Escargueil, Alexandre; Lami, Raphaël (Frontiers in Marine Science, 2017)
Posidonia oceanica (L.) Delile is an endemic Mediterranean seagrass angiosperm. The taxonomic diversity of the Posidonia-associated microbiota has previously been inventoried using culture-based and culture-independent approaches. However, little is known about the type of chemical interactions that occur between the cells within this microbiota. In this study, we isolated 60 bacterial strains from the leaves and rhizomes of P. oceanica and evaluated their capacity to communicate through quorum sensing. We found 6 strains able to emit 8 different types of quorum sensing acyl homoserine lactones, identified through UHPLC-HRMS/MS after bioguided fractionation of large cultures. We also identified 19 strains able to produce furanosyl diester borate, another type of quorum sensing autoinducer. Also, 5 strains were found to produce quorum quenching compounds. Finally, as quorum sensing is known to be involved in biofilm production, we also tested whether strains positive to our biotests were able to produce biofilms. Collectively, these data reveal the importance of examining chemical interactions within this bacterial consortium associated with P. oceanica that could have an impact on the physiology of this key Mediterranean seagrass.